Bokser i śmierć. Konwencja filmu bokserskiego a opowiadanie o Auschwitz - Mąka-Malatyńska, Katarzyna (Załącznik Kulturoznawczy, 2022)
The author shows Solan’s work The Boxer and Death against the background of Czechoslovakian cinematography productions of the time and interprets it in relation to the literary prototype – a short story by Józef Hen. An important analytical and interpretative context are other film works about boxers-prisoners in concentration camps and sports film conventions.